Analysis of Tourists’ Interest in Visiting Destinations Around Ubud, Bali, Through Perceptions of Overtourism, Preferences for Alternative Destinations, and the Search for Authentic Experiences - Paramita Andiani; Alifah Lettiane Virainy Lubis; Ilham Akbar Bunyamin (West Science Social and Humanities Studies, 2026)
This study aims to analyze tourists’ interest in visiting destinations around Ubud through perceptions of overtourism, preferences for alternative destinations, and the search for authentic experiences. The increasing concentration of tourists in major tourism destinations has generated various issues related to overcrowding, environmental pressure, and declining travel comfort, encouraging tourists to seek alternative tourism experiences outside mainstream destinations. This research employed a quantitative approach using a survey method involving 250 respondents consisting of domestic and international tourists who had visited or planned to visit destinations around Ubud, Bali. Data were collected through questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The findings indicate that overtourism perception significantly influences tourists’ preference for alternative destinations and authentic experience seeking. Furthermore, preference for alternative destinations and authentic experience seeking were found to positively and significantly affect tourists’ visiting interest. The results suggest that tourists increasingly prefer destinations that offer lower crowd density, environmental comfort, cultural immersion, and meaningful tourism experiences. This study contributes to sustainable tourism literature by explaining the behavioral transformation of tourists in response to overtourism conditions in popular tourism destinations. The findings also provide practical implications for tourism destination managers and policymakers in developing sustainable tourism strategies through destination diversification and preservation of authentic local experiences in Bali tourism.